Sorting a large set of heavily used LiF:Mg, Ti thermoluminescent detectors into repeatable subsets of similar response. (January 2015) - Kearfott, Kimberlee J.; Newton, Jill P.; Rafique, Muhammad
Abstract: A set of 920 heavily used LiF:Mg, Ti thermoluminescent dosimeters (TLDs) was placed into a polymethyl methacrylate (PMMA) plate attached to a 40×40×15 cm 3 PMMA phantom and irradiated to 4.52 mGy using a 137 Cs source. This was repeated three times to determine the mean and standard deviation of each TLD׳s sensitivity. Reader drift was tracked over time with 10 control dosimeters. Two test sets of 100 TLDs were divided into subsets with sensitivities within ±1% of their subset means. All dosimeters were re-irradiated four times to test the TLDs׳ response repeatability and determine the sensitivity uniformity within the subsets. Coefficients of variation revealed that, within a given subset, the dosimeters responded within ±2.5% of their subset mean in all calibrations. The coefficient of variation in any of the 200 TLDs׳ calibrations was below 6% across the four calibrations. The work validates the approach of performing three calibrations to separate heavily used and aged TLDs with overall sensitivity variations of ±25% into subsets that reproducibly respond within ±2.5%. Highlights: Study aims for transformation of an old, heavily used, possibly damaged set of TLDs into a usable, uniformly responding set. The work validates the approach of performing three calibrations to separate heavily used TLDs with variability of ±25% into sets that reproducibly respond within ±2.5%.